From a Germylene to an "Inorganic Adamantane": [Ge4(μ‐O)2(μ‐OH)4W(CO)54]·4THF1. Issue 30 (23rd September 2015) - Kitschke, Philipp; Mertens, Lutz; Rüffer, Tobias; Lang, Heinrich; Auer, Alexander A.; Mehring, Michael
Abstract: Germanium(II) (2‐methoxyphenyl)methoxide (1 ) and [W(CO)5 (thf)] gave rise reproducibly (79 % yield) to a new, uncharged transition‐metal complex of a germanium(II) hydroxido oxido cluster – [Ge4 (μ‐O)2 (μ‐OH)4 W(CO)5 4 ]· 4THF (2· 4THF) – as a product of hydrolysis. The germylene1 is monomeric in solution at ambient temperature but forms dimers in solution at low temperatures and in the solid state. Dimerization of compound1 was studied by 1 H NMR spectroscopy and with the aid of DFT‐D calculations. The tetranuclear cluster2 shows an adamantane‐like core structure with coordination of tungsten pentacarbonyl to germanium(II) in the solid state as well as in solution. Characterization of both compounds, including by single‐crystal X‐ray diffraction analysis, by 1 H NMR, 13 C 1 H NMR, FTIR spectroscopy, and through thermal analyses, is presented. Abstract : Germylene1 and [W(CO)5 (thf)] gave rise to2, a transition‐metal complex of a germanium(II) hydroxido oxido cluster, after hydrolysis. Germylene1 is monomeric in solution at ambient temperature but forms dimers at low temperatures in solution and in the solid state. Cluster2 has an adamantane‐like structure based on a Ge4 O2 (OH)4 core, thus complementing the series of "inorganic adamantanes".